2018
DOI: 10.1007/s11657-018-0433-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkyphotic measures using distance from the wall: validity, reliability, and distance from the wall to indicate the risk for thoracic hyperkyphosis and vertebral fracture

Abstract: C7WD is valid and reliable with good diagnostic properties for thoracic hyperkyphosis and vertebral fracture. The findings confirm the use of C7WD using traditional ruler-based method as a practical tool to screen and monitor severity of thoracic hyperkyphosis in clinics and communities. In addition, the measurement using the IG-KypDisT provided accurate data that can be saved for further analysis; it is therefore suggested for research settings. The findings would promote the standardization of hyperkyphosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…It has been reported that the KMD data measured with the rulers were susceptible to errors due to their misalignment. 10 , 11 , 14 Thus, the KMD data measured with rulers in this study were verified using IG-KypDisT [Patent Application No. 1701004049; Fig.…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…It has been reported that the KMD data measured with the rulers were susceptible to errors due to their misalignment. 10 , 11 , 14 Thus, the KMD data measured with rulers in this study were verified using IG-KypDisT [Patent Application No. 1701004049; Fig.…”
Section: Methodsmentioning
confidence: 69%
“…Of all the existing hyperkyphosis measures, the occiput–wall distance (OWD) is a practical measure that can be executed easily using two rulers to measure the perpendicular distance from the landmark to the wall while standing against it. 11 , 12 However, the OWD faces some criticisms, including the following: using the occiput as a landmark could confound data interpretation regarding thoracic hyperkyphosis and increase the chance of errors due to individuals moving their heads, having forward head posture, and the varying shapes of the skulls. 10 , 13 , 14 Moreover, the data taken from two rulers were susceptible to errors due to their misalignment, e.g., not parallel to the landmark and not perpendicular to the wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each test was performed three times and the best trial was used [ 22 ]. The distance (cm) between the seventh cervical vertebra (C7) and the wall was measured by a folding ruler to estimate the back-straightening ability [ 23 ]. Body height was measured with a stadiometer and body weight with a digital scale.…”
Section: Methodsmentioning
confidence: 99%
“…The second method requires the usage of two rulers, one to be placed parallel to the C7 prominence and the other to quantify the perpendicular distance from the alignment of the first ruler to the wall. 14 12,18,19 Forward Head Posture and The Muscles…”
Section: Postural Changes In Forward Head Posturementioning
confidence: 99%